Differential effects of Swedish active labour market programmes for unemployed adults during the 1990s - Barbara Sianesi (Institute for Labour Market Policy Evaluation (IFAU), 2002)
The paper evaluates the differential performance of the six main types of Swedish programmes that were available to adult unemployed workers entitled to unemployment benefits in the 1990s: labour market training, workplace introduction, work experience placement, relief work, trainee replacement and employment subsidies. On the basis of a large and particularly rich administrative dataset, propensity score multiple-treatment matching methods are applied to investigate the differential performance of the programmes both relative to one another and vis-à-vis more intense job search in open unemployment. Outcomes being assessed are short- and long-term employment rates as well as the probability of collecting unemployment benefits over time. Compared to waiting longer in open unemployment, all the programmes initially reduce their participants employment probability in the short term (lock-in effect). Positive findings on more long term employment prospects are confined to job subsidies alone. Participation in trainee replacement makes no difference to deputies subsequent labour market outcomes. Individuals joining any of the remaining programmes later display either the same (workplace introduction) or lower employment rates coupled with a higher benefit collection probability than if they had searched further as openly unemployed. A likely factor behind these disappointing results is the use of such types of programmes simply as a way to re-qualify for unemployment benefits. As to the pair-wise comparison of the six programmes, the central finding is again that the more similar a programme is to a regular job, the higher the programmes benefits to its participants, with employment subsidies by far the best performer, followed by trainee replacement. Several macroeconomic studies have however documented large and negative displacement and dead-weight effects for exactly these types of programme, which highlights the difficult trade-off faced by labour market policy.
Keywords: C14; J38; J65; J68; 330; active labour market programmes; evaluation; multiple-treatment matching; treatment effects